Nanotoxicological study of downconversion Y2O3:Eu3+luminescent nanoparticles functionalized with folic acid for cancer cells bioimaging - Chávez García, Dalia H. (My University, 2020)
Luminescent lanthanide downconversion nanoparticles (DCNPs) provide a combination of high luminescence intensity, sharp emission peaks with narrow bandwidth and a large Stokes' shift, leading to high‐performance biomedical applications mainly for imaging. The purpose of this study is to present a nanotoxicological study of DCNPs Y2O3 codoped with Eu3+ and functionalized with folic acid (FA). These assessments include cytotoxicity, genotoxicity, hemocompatibility, and in vitro inflammatory studies. We demonstrated by flow cytometry and confocal microscope the internalization of FA‐DCNPs in breast cancer and melanoma cells. They were synthesized by sol–gel method and coated with a thin silica shell to make them biocompatible; also they were functionalized with amino groups and FA ligands that bind to the folate receptors (FR) located on the surface of the cancer cells studied. This functionalization enables the DCNPs to be internalized into the cancer cells via endocytosis by the conjugation FA‐FR. The DCNPs were characterized with transmission electron microscope, Fourier transform infrared spectroscopy and photoluminescence. The nanotoxicological assessments demonstrated that both nanoparticles (bare and functionalized) are no cytotoxic and no genotoxic at the tested concentrations (0.01–20 μg/mL) in three cell lines (breast, skin cancer, and osteoblasts). Also they are hemocompatible and do not exert nitric oxide production in vitro by macrophages. The FA‐DCNPs were clearly localized into the cell cytoplasm with bright red luminescence. Thus, herein we present a complete nanotoxicological study of FA‐DCNPs Y2O3 codoped with Eu3+ and we conclude that these nanoparticles are biocompatible and can be further used for cancer cells bioimaging.
Journal of biomedical materials research part B
Keywords: Cell culture; Nanobiology; Nanotechnology; Campus Ensenada